Antara Solidaritas dan Komodifikasi: Analisis Wacana Kritis terhadap Narasi THR untuk Ojol di Media Massa Online - Octaviana, Sheila (UI Scholars Hub, 2025)
This article examines the discourse surrounding the distribution of religious holiday bonuses (THR) for online motorcycle taxi (ojol) drivers in Indonesian media using Norman Fairclough’s Critical Discourse Analysis (CDA) framework. The study reveals that the THR issue extends beyond legal and policy debates, becoming a contested site of meaning among platform companies, the state, media, and drivers. At the micro level, semantic strategies, such as the use of terms like “bonus,” “partner,” and “assistance”,obscure drivers’ legal employment status. At the meso level, corporations and the state dominate discourse production through mainstream media, while drivers’ voices are often marginalized. At the macro level, the discourse is shaped by neoliberal ideology, emphasizing flexibility and meritocracy while downplaying companies’ social responsibilities. The state acts more as a symbolic facilitator than as a substantive regulator. The article concludes that digital labor inequality is reproduced not only through policy structures but also via discursive practices that normalize worker subordination.